Women, Gender, and the Palace Households in Ottoman Tunisia - Kallander, Amy Aisen, 1978- (Book collections on Project MUSE., 2013)
This examination of Tunisia's ruling family between 1700 and 1900 reveals the significance of the palace and the crucial political and economic roles women played in the family's relationship with the imperial government.